2010
DOI: 10.1186/1472-6947-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of features of electronic prescribing systems to support quality and safety in primary care using a modified Delphi process

Abstract: BackgroundElectronic prescribing is increasingly being used in primary care and in hospitals. Studies on the effects of e-prescribing systems have found evidence for both benefit and harm. The aim of this study was to identify features of e-prescribing software systems that support patient safety and quality of care and that are useful to the clinician and the patient, with a focus on improving the quality use of medicines.MethodsSoftware features were identified by a literature review, key informants and an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 18 publications
(23 reference statements)
1
34
0
Order By: Relevance
“…This is similar to the work done by Coombes et al [17] and Millar et al [22]. The safety features which have achieved consensus in this study to be included in a neonatal and paediatric prescription chart, can furthermore be investigated with regards to their implementation in electronic prescribing and medication administration systems, similar to the work done by Sweidan et al [68]. The authors of the report ''Standards for the design of hospital in-patient prescription charts'' describe the safety features to be equally applicable to paper and electronic charts [20].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This is similar to the work done by Coombes et al [17] and Millar et al [22]. The safety features which have achieved consensus in this study to be included in a neonatal and paediatric prescription chart, can furthermore be investigated with regards to their implementation in electronic prescribing and medication administration systems, similar to the work done by Sweidan et al [68]. The authors of the report ''Standards for the design of hospital in-patient prescription charts'' describe the safety features to be equally applicable to paper and electronic charts [20].…”
Section: Resultssupporting
confidence: 75%
“…The authors of the report ''Standards for the design of hospital in-patient prescription charts'' describe the safety features to be equally applicable to paper and electronic charts [20]. Sweidan et al [68] have identified features of e-prescribing that support patient safety and quality of care and have used the modified Delphi process to reach consensus on the expected impact of the features in four domains: patient safety, quality of care, usefulness to the clinician and usefulness to the patient. Further research would be required to investigate why 17 safety features such as height, and body surface area did not achieve consensus.…”
Section: Resultsmentioning
confidence: 99%
“…Two papers reported on adverse events with a focus on medication error [ 43 , 44 ]. Both the papers related to information technology to improve patient safety and quality of care.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the past research on the outcomes and impacts of e-prescribing systems has focused on doctors and physicians as the samples. 9,22,29,30 However, the research on the effect of e-prescribing systems in community pharmacy practice is sparse, compared to that on physicians' use in hospital settings. 1,18 Community pharmacists in particular face more problems in adopting and using e-prescribing systems.…”
Section: Introduction and Research Gapmentioning
confidence: 97%